The effect of workplace spirituality on organization citizenship behavior for the environment mediated by environmental passion - Arrohma Kholifatun Ni’mah; Annida Unnatiq Ulya (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This study aims to determine the effect of workplace spirituality Citizenship Behavior on the Environment (OCBE) with environmental passion as a mediating variable. The object of research in this study is the employees of CV New Tweety Magetan. This research method uses quantitative research methods with the help of the SPSS 23 application as a data processing tool. Data analysis techniques in this study used regression analysis techniques and the Sobel test for intervening variable. The sampling technique uses a nonprobability sampling technique. The sample in this research is 108 respondents. The findings of this study indicate that environmental passion has the greatest influence with a coefficient value of 0.576. The conclusion from this study is that workplace spirituality has a significant positive effect on environmental passion, workplace spirituality, and environmental passion have a significant positive effect on OCBE, and workplace spirituality has a significant and indirect effect on OCBE through the mediation of environmental passion. Then companies can consider facilitating spiritual practices that are in line with environmental values ​​and increase the spirit of protecting the environment among employees to enhance sustainable organizational citizenship behavior and organizational performance